UK consensus recommendations on the management of oral epithelial dysplasia during COVID-19 pandemic outbreaks. (January 2021) - McCarthy, Caroline Elizabeth; Fedele, Stefano; Ho, Michael; Shaw, Richard
Highlights: Consensus Guidelines have been developed for the management of OED through a pandemic outbreak. Risk stratification is suggested so that high-risk cases are prioritised for face-to-face review. Remote consultations may be a useful method for ensuring continuity of review for lower risk cases. Abstract: Objectives: Oral Epithelial Dysplasia (OED) is associated with an increased risk of oral cancer development. The SARS-CoV-2 pandemic is necessitating the suspension or dramatic reduction of face-to-face non-urgent elective services, including OED clinics. Little is known regarding the potential impact of elective services suspension upon the risk of OED progression, and whether alternative strategies (e.g. remote consultations) may be introduced to ensure OED surveillance. The aim of this paper is to provide expert-opinion consensus recommendations for the management of OED during the current and future pandemic outbreaks. Materials and methods: A working group of nine UK-based senior clinicians and academics in Oral and Maxillofacial Surgery and Oral Medicine was created and twelve consensus statements were developed using a modified-Delphi process. Greater than 80% agreement was considered a consensus. Results: Consensus was achieved for all twelve statements (89–100% agreement). The group agreed that, during the temporary suspension of elective services associated with COVID-19 pandemic outbreaks, patients with OED can be risk stratified to determine the length of accepted delay in face-to-face consultation. Remote consultations with patient-provided clinical photographs may be a useful way of maintaining a level of surveillance in this group of patients. Conclusions: Using an expert working group methodology, we have developed consensus recommendations for the monitoring of individuals with OED during pandemic outbreaks associated with temporary suspension of elective services. This has identified areas of future research and highlighted the need for a stronger evidence base to inform the set-up and delivery of surveillance regimens for patients with OED.